Family Conflict in the Context of Economic Change: Resilience and Adaptation - Rohman, Miftakur (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research aims to explore the dynamics of family conflict arising from economic changes and how families can demonstrate resilience and adapt. In a rapidly changing social context, a deeper understanding of how economic factors influence interactions within families becomes increasingly important. The method used in this study is a qualitative approach, conducting in-depth interviews with 30 respondents who are heads of families from various economic backgrounds, ranging from low to middle income. The main findings of this research indicate that economic changes, such as inflation and unemployment, significantly contribute to the increased conflict within households. This is evident in the rising tension often triggered by unstable financial factors. However, interestingly, families with strong social support mechanisms, such as solid networks of friends and family, tend to show higher levels of resilience amidst crises. The results of this research have important implications for understanding the relationship between economic dynamics and family life, as well as providing significant recommendations for social policies to support families in facing increasingly complex economic challenges. With the right approach, it is hoped that family and community well-being can be enhanced overall.